2020
DOI: 10.3390/ijerph17197340
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’ Mental Health in the Midst of COVID-19 Pandemic: The Roles of Work Demands and Recovery Experiences

Abstract: The COVID-19 pandemic potentially increases doctors’ work demands and limits their recovery opportunity; this consequently puts them at a high risk of adverse mental health impacts. This study aims to estimate the level of doctors’ fatigue, recovery, depression, anxiety, and stress, and exploring their association with work demands and recovery experiences. This was a cross-sectional study among all medical doctors working at all government health facilities in Selangor, Malaysia. Data were collected in May 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 54 publications
5
51
1
3
Order By: Relevance
“…Some doctors reported positive emotions: pride in their work, relief and hope as the worst-case scenarios of overwhelming COVID-19 cases did not come to pass, and inspiration when surrounded by their dedicated peers and colleagues. Negative emotions also came across strongly in interviews—fear, guilt, sadness, frustration—similar to those expressed in studies of other frontline staff working in COVID-19 [ 1 , 2 , 3 , 4 , 5 ]. These negative emotions can all build up into emotional exhaustion, which is a major component of burnout [ 31 ], a serious concern for health workers during COVID-19, as the World Health Organisation has recently identified [ 9 ].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Some doctors reported positive emotions: pride in their work, relief and hope as the worst-case scenarios of overwhelming COVID-19 cases did not come to pass, and inspiration when surrounded by their dedicated peers and colleagues. Negative emotions also came across strongly in interviews—fear, guilt, sadness, frustration—similar to those expressed in studies of other frontline staff working in COVID-19 [ 1 , 2 , 3 , 4 , 5 ]. These negative emotions can all build up into emotional exhaustion, which is a major component of burnout [ 31 ], a serious concern for health workers during COVID-19, as the World Health Organisation has recently identified [ 9 ].…”
Section: Discussionsupporting
confidence: 66%
“…Some work such as administrative tasks and meetings which previously needed to be done physically in the hospital was changed to be undertaken at home during the lockdown, which also allowed doctors to spend more time at home. This enabled respondent doctors to achieve a better work–life balance, and to improve their diets and exercise levels (as Sean, Bridget and Fiona did), similar to findings from a survey of Malaysian doctors [ 3 ]. Evidence suggests that exercise levels have increased across the general population globally during COVID-19 lockdowns [ 50 ], and doctors may be following this general trend.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…During COVID-19, feelings that there was inadequate PPE supply at their hospital was associated with worse psychological outcomes [ 107 , 143 , 147 , 157 , 163 , 165 , 170 , 178 , 187 , 188 ]. Physicians working more days, with higher patient volumes, or with increased duties than before than pandemic also had an increased prevalence of psychological symptoms [ 96 , 101 , 122 , 128 , 149 , 187 , 192 , 195 , 198 ]. Eighteen studies reported on insomnia [ 32 , 35 , 36 , 54 , 65 , 69 , 88 , 114 , 128 , 145 , 149 , 163 , 175 , 177 , 181 , 188 , 192 , 194 ], which is associated with psychiatric disorders and is a risk factor for depression and anxiety [ 15 , 32 , 54 , 65 , 69 , 199 , 200 ].…”
Section: Resultsmentioning
confidence: 99%
“…This review also found that fear of uncertainty or becoming infected was one of the biggest challenges healthcare workers had to cope with [ 7 ]. Other factors such as the frequent growth of COVID-19 cases and deaths due to the disease, lack of resources (material and human), unspecific and ineffective treatments, in addition to an increase in work demands are known to contribute to healthcare workers’ exhaustion and mental health deterioration [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%